Insertion en emploi de jeunes diplômés : diversité, compromis et incertitudes - Fournier, Geneviève (Canadian Journal of Counselling and Psychotherapy, 2007)
This article describes the experience of a group of recent graduates during the first three years of integration into the labour market. The sample consists of a group of 150 new workers, interviewed three years after their graduation from high school career programs, college technical programs and university undergraduate programs. The findings of this study highlight four commonalities in the process of social and professional integration: a diversified balance between personal and professional life, the unpredictability of significant events, the importance of a support network, and the many impacts of this life stage on the way in which the subjects experience work and on their life as a whole.